PENGARUH KOMPETENSI APARAT PENGELOLA DANA DESA, KOMITMEN ORGANISASI PEMERINTAH DESA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KABUPATEN 50 KOTA (Studi Empiris Pada Kecamatan Harau, Kecamatan Pangkalan Koto Baru, Dan Kecamatan Kapur IX) - Aulia, Putri; Agusti, Restu; Julita, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The accountability of village fund management has become a demand for local government. The existence of this demand results from the implementation of Law No. 6 of 2014 on the Village. The management of village funds in City 50 Regency is still far from the expectations. Problems emerging from the accountability of village fund management are related to the competence of village fund management officers, the commitment of village government organizations, utilization of information technology and community participation. This research aims to know and analyze the influence of competence of village fund management officer, commitment of village government organization, utilization of information technology and public participation to accountability of village fund management in City 50 Regency. This is a quantitative research study and data were collected by surveys or questionnaires. Population and sample are village fund management officers in City 50 Regency with 96 respondents. The hypothesis was tested by multiple linear regression analysis with SPSS application. The findings show that: (1). The competence of village fund management officers has a positive and significant impact on the accountability of village fund management; (2). The commitment of village government organizations has a positive and significant impact on the accountability of village fund management; (3). utilization of information technology has a positive and significant impact on the accountability of village fund management; (4) Community participation has a positive and significant impact on the accountability of village fund management. The coefficient of determination 0,866. This shows that the influence of independent variables namely: the JOM FEB, Volume 1, Edisi 1 (Januari – Juni 2018) 2 competence of the village fund management officer, the commitment of the village government organization, utilization of information technology and the participation of the society, towards the dependent variable (the accountability of village fund management) explained by the equation model in this research is 86,6%. While the rest 13,4% is explained by other factors which are not included in this model. The implications of this study are to encourage the accountability of village fund management through the increased competence of village fund management officers, village government organizational commitment, and community participation.Keywords : Competence of village fund management officers, Commitment of village government organization, Utilization of information technology, Community participation, accountability of village fund management.